Imbak canyon conservation area, Sabah - Paul Porodong; Gaim James Lunkapis; Fadilah Sarbi (Academy of Sciences Malaysia , Yayasan Sabah, 2011)
Success of conservation effort should not only be measured by the size of an area managed but how far we are willing to recognise the significance of interaction between local people and their environment.